Sol-gel synthesized TiO2-chitosan nanocomposite as antibacterial coating for orthopedic implants: Investigation of properties and antimicrobial mechanisms - Huan Min; Yi Wu; Jiabin Wen; Jia Guo; Sicong Jiang; Jinhui Cheng (Alexandria Engineering Journal, 2025)
This study investigates the development of surface-modified titanium alloy implants through sol-gel synthesis to prevent bacterial infections while maintaining biocompatibility. The optimized 50:50 TiO₂:chitosan nanocomposite coating exhibited superior performance characteristics, with AFM analysis revealing controlled surface topography Ra = 78 ± 7 nm) and uniform particle distribution. Electrochemical measurements demonstrated enhanced corrosion resistance, with impedance modulus increasing from 3.2 × 10⁵ Ω·cm² for uncoated Ti6Al4V to 2.8 × 10⁶ Ω·cm² for the optimized coating at 0.01 Hz. The coating showed excellent mechanical stability with an adhesion strength of 15.4 MPa and critical load of 18.5 N. Live/dead bacterial staining and CLSM analysis revealed significant reduction in biofilm formation, with time-dependent studies showing rapid initial bacterial inhibition within 6 h (68.7 % for S. aureus, 64.5 % for E. coli) and sustained antimicrobial activity over 72 h (95.2 % for S. aureus, 93.1 % for E. coli). The coating maintained structural integrity and performance after 30-day immersion in simulated body fluid, demonstrating its potential for long-term implant protection.